Underwater propeller turbine blade redesign based on developed inverse design method for energy performance improvement and cavitation suppression. (1st June 2023) - Lu, Yeming; Guo, Zhenyang; Zheng, Zeyu; Wang, Wei; Wang, Hui; Zhou, Fangming; Wang, Xiaofang
Abstract: This paper conducts a systematic study to optimize the high-speed propeller turbine blade with high energy losses and severe cavitation. The trubine blade takes the role to provide the sustainable power for the underwater vehicle, whose structure is complex and crucial. To redesign the blade effectively, a developed inverse design method to generate various design schemes has been adopted with the union of the derived constrained zone and the one-dimensional theory. Established on the design method, a design procedure comprised of the CFD simulation, the LHS sampling, the multi-source constrained screening, the Kriging model, and the MOPSO algorithm was proposed. By setting energy performances (thrust, consuming power) and the cavity size as the objectives, the adaptive optimization of the runner blade installed on the underwater vehicle has been implemented, and two optimized models were finally designed out. Via further comparative analysis of the original and the redesigned blades, the maximum thrust increasement is 6.6%, the maximum power reduction is 3.1%, while the maximum cavity size reduction can be as much as 2.67%. Moreover, there exists a large structural difference for the runner blade before and after optimization, which could provide multiple options for further application. Finally, the specific inner flow analysis consisted of the performance calculation at different cruising speeds, and 3D analysis of key flows fields has been applied to reveal the reason to improve the performance and suppress the cavitation. Further, the energy balance theory was adopted to extract the specific losses at different hydraulic components, which demonstrates that the optimized propeller turbine blades can improve the energy performance. The study is expected to provide a technical reference for the energy performance improvement and cavitation suppression of the high-speed turbine machinery. Highlights: A developed inverse design method to redesign the high-speed rotating propeller turbine. The multi-objective adaptive design system for high-speed rotating propeller turbine blade models was established. The joint operating characteristics of the rotating and the underwater vehicle was evaluated. The energy performance improvement and cavitation suppression effects were analyzed.